Lipid profile and redox status in high performance rhythmic female teenagers gymnasts - Guerra, A.; Rego, C.; Laires, M. J.; Castro, E. M.; Silva, D.; Monteiro, C.; Silva, Z.; Lebre, E.; Bicho, M. (The Journal of Sports Medicine and Physical Fitness, 2001)
The aim of the present study is to evaluate the lipid profile and some parameters of oxi-redox status in a group of teenage female athletes. All gymnasts of the Portuguese National Team of Rhythmic (n=20) were included in the study. A group of untrained healthy female adolescents, matched for age, was also included (n=28). METHODS: Auxology, nutritional status and body composition were evaluated as well as biological parameters, dietary and training habits. Statistics included descriptive analysis, t-Student and Mann-Whitney for comparative study, and Pearson and Spearman correlations, according to variable distribution. RESULTS: Chronological age was 14.3+/-1.7 and 14.6+/-1,7 years, respectively for gymnasts and untrained adolescents. Gymnasts showed lower body mass index (p<0.001) and fat mass (p<0.001) and also a hypoenergetic diet, with higher supply in protein (p<0.05) and saturated fat (p<0.01). Lipid profile showed higher HDL-cholesterol (p<0.01) and lower apo B values (p<0.001) in gymnasts, compared to untrained. Red blood cell's enzymes studied were higher for transmembrane NADH reductase of ferricyanide (TMR), (p<0.01), methaemoglobin reductase (MetHbRed), (p<0.01), and low-molecular weight protein tyrosine phosphatase (LMW-PTP), (p<0.0001) in untrained adolescents. Susceptibility of LDL to peroxidation (LDL-TBARS) were higher in gymnasts (76.3+/-20.3 &mgr;M/l versus 35+/-21.7 &mgr;M/l), (p<0.001). Correlations were positive and significant in both gymnasts and untrained, between LDL-TBARS and LDL-cholesterol (r=0.674, p<0.01 and r=0.544, p<0.05 respectively) and apolipoprotein B (r=0.721, p<0.001 and r=0.659, p<0.01, respectively). LDL-TBARS were negative and significatively correlated to TMR (t=-0.608; p<0.01) only in gymnasts. CONCLUSIONS: The authors conclude that the practice of intense physical exercise in rythmic gymnasts induces a compromise of nutritional status and unbalanced food habits. The intensive exercise also induces not only a protective lipid profile, but also a higher lipid peroxidation. Further prospective studies are important to evaluate the influence of intensive training on atherosclerosis development.